Why do borrowers pledge collateral? New empirical evidence on the role of asymmetric information - Allen N. Berger; Marco A. Espinosa-Vega; W. Scott Frame; Nathan H. Miller (Federal Reserve Bank of Atlanta, 2007)
An important theoretical literature motivates collateral as a mechanism that mitigates adverse selection, credit rationing, and other inefficiencies that arise when borrowers hold ex ante private information. There is no clear empirical evidence regarding the central implication of this literature - that a reduction in asymmetric information reduces the incidence of collateral. We exploit exogenous variation in lender information related to the adoption of an information technology that reduces ex ante private information, and compare collateral outcomes before and after adoption. Our results are consistent with this central implication of the private-information models and support the empirical importance of this theory.
Keywords: G21; D82; G32; G38; 330; collateral; asymmetric information; banks; small business; credit scoring; Kreditsicherung; Asymmetrische Information; Kreditrationierung; KMU; Kreditwürdigkeit; USA